PENTINGNYA METODOLOGI PENDIDIKAN ISLAM DALAM PROSES BELAJAR MENGAJAR - Budi, Irwan Setia (STIT AL MULTAZAM, 2022)
Islamic education methodology is a method that has been taught by the Prophet in the learningprocess. In this Islamic education method there are several important methods that we must know,namely the lecture method, the question and answer method, the discussion method and the habituation method. Of the several methods, there are advantages and disadvantages of each of these methods. Therefore, this method of Islamic education is very important to be known and mastered by teachers. To achieve learning objectives, of course, teachers must always be active in the selection of learning methods. because the capacity of students / student absorption is very different, students with one another of course there are differences, not all of them can be said to be equal. well here demands for teachers to be clever in the selection of learning methods so that students can absorb all subject matter perfectly and it can be said that learning is successful.